Kajian Penuaan pada Lansia Serta Profil Antioksidan Secara Kualitatif di Kelurahan Sukarame Bandar Lampung - Regina Callista A. Tupamahu; Harliansyah Harliansyah; Kuslestari Kuslestari (Publikasi Indonesia, 2022)
The aging process that feeled by elderly will cause a decrease in functional and cellular functions. The factors that influence this process are divided into two factors, internal factors such as free radicals and external factors such as lifestyle, environment, and food. Free radicals in the body can be neutralized by antioxidants that come from a good lifestyle and foods that contain antioxidants. This study uses a qualitative ethnographic method by conducting interviews using a questionnaire combined with respondent observations. The questionnaire used is divided into three analyzes, there are symptom analysis, lifestyle analysis, and food analysis. Then the scores on the three analyzes will be added up and produce qualitative conclusions. The sample was determined by purposive sampling with analysis of the relationship between each of independent variables using a correlation test using SPSS application. The symptoms and the lifestyle lived by the elderly in Kelurahan Sukarame, Bandar Lampung play an important role in the personal antioxidant profile while the food intake chosen by the elderly has a lower role than symptoms and lifestyle. Physical activities such as exercise and morning walks and minimizing UV exposure with a combination of taking vitamin supplements routinely will maximize the aging process of the elderly in Kelurahan Sukarame, Bandar Lampung.